Comment s'écrit l'autre? Sources épigraphiques et papyrologiques dans le monde méditerranéen antique - Ruiz Darasse, Coline (PrimaLun@, 2020)
Two people who do not speak the same language meet. One writes the name of the other: a fugitive, timeless and banal scene. Only a modest written record remains. Thanks to it, however, we can, centuries later, re-experience the exact moment of this exchange. Sometimes the fugitively captured name will be the only vestige of completely extinct languages. For epigraphies of fragmentary attestation, understanding that it is a proper name, isolating it and deciphering it is in itself a first task. It is then necessary to analyze the treatment of this name in the language of reception, the required adaptations and retrace the context in which the object was written. With these few pieces, the background image of the cultural and linguistic puzzle of ancient societies is reconstituted. This book aims to constitute and leaf through the album of a dozen of these linguistic snapshots all around the ancient Mediterranean.